2003
DOI: 10.1046/j.1529-8817.2003.02178.x
|View full text |Cite
|
Sign up to set email alerts
|

PHYLOGENY OF PHAGOTROPHIC EUGLENIDS (EUGLENOZOA): A MOLECULAR APPROACH BASED ON CULTURE MATERIAL AND ENVIRONMENTAL SAMPLES1

Abstract: Molecular studies based on small subunit (SSU) rDNA sequences addressing euglenid phylogeny hitherto suffered from the lack of available data about phagotrophic species. To extend the taxon sampling, SSU rRNA genes from species of seven genera of phagotrophic euglenids were investigated. Sequence analyses revealed an increasing genetic diversity among euglenid SSU rDNA sequences compared with other well‐known eukaryotic groups, reflecting an equally broad diversity of morphological characters among euglenid ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 62 publications
0
24
0
Order By: Relevance
“…Peranemida have a type III apparatus (curved vanes, 2 rods with internal microtubules). The position of Dinema was not resolved previously (Busse, Patterson, and Preisfeld 2003), but we have shown that it groups with Anisonema and Peranema sp. with 96–99% support.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Peranemida have a type III apparatus (curved vanes, 2 rods with internal microtubules). The position of Dinema was not resolved previously (Busse, Patterson, and Preisfeld 2003), but we have shown that it groups with Anisonema and Peranema sp. with 96–99% support.…”
Section: Discussionmentioning
confidence: 56%
“…2 largely bacteriotrophic Petalomonadida are the earliest diverging euglenoids. Except for the robust sister relationship between Euglenida and Eutreptiida (previously found by Brosnan et al 2003; Marin et al 2003; and Busse, Patterson, and Preisfeld 2003), the branching order of the six euglenoid orders is poorly resolved, suggesting rapid early radiation among the phagotrophs and/or near mutational saturation.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Later 18S rDNA analyses with increased representation of phagotrophic euglenids typically provided little‐to‐no support for a basal position of petalomonads (Busse et al. ; von der Heyden et al. ).…”
Section: Discussionmentioning
confidence: 99%